Detection the Serogroups of Escherichia coli isolates from Urine sample of UTI patients - Fakhri S.Ahmed Ph.D (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aims: Determining of E.coli serogroups which isolation from UTI patientsPatients and Methods: the study was conducted between September 2019 to April 2020 and they wascollected 40 sample from patient how are diagnosis with UTI during this study .Results: From the UTI patients individuals, 40 strains were identified in which O serogroups showed8(30%) and 2 (20%), respectively, of occurrence in those strains. Moreover, the enterohemorrhagic E. coli(O157 H7) and the enteroaggregative E. coli (O44 H7) were detected in two strains of the UTI-based urinesamples only. For the antibiotic resistance properties of the biofilm positive producers isolated from the UTIurine samples, multidrug resistance was revealed in 60% of those isolates; however, only 20% of the biofilmnegative producers from the UTI urine samples showed the MDR characteristics. Biofilm was identified in75% of the UTI urine. For the antibiotic sensitivity test, the results demonstrated that the sensitivity rates toImipenem, Amikaci, gentamicin, and tobramycin were 90%, 100%, 65%, and 40%, respectively, in the UTIstrains.Conclusion: The herein study provides thorough data about the Escherichia coli based biofilm,